2004
DOI: 10.1097/01.shk.0000129759.58490.d6
|View full text |Cite
|
Sign up to set email alerts
|

TOLL-LIKE RECEPTOR 4 COUPLED GI PROTEIN SIGNALING PATHWAYS REGULATE EXTRACELLULAR SIGNAL-REGULATED KINASE PHOSPHORYLATION AND AP-1 ACTIVATION INDEPENDENT OF NFκB ACTIVATION

Abstract: Previous studies have implicated heterotrimeric Gi proteins in signaling leading to inflammatory mediator production induced by lipopolysaccharide (LPS). TLR4 has recently been shown to play a central role in response to LPS activation. We hypothesized that Gi proteins are coupled to TLR4 activation of signaling pathways. To inhibit Gi protein function, human embryonic kidney (HEK) 293 cells or RAW 264.7 cells were pretreated with pertussis toxin (PTx), an inhibitor of receptor-Galphai interaction, or transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 37 publications
1
49
2
Order By: Relevance
“…This is in contrast to neutrophils recovered from TLR4-deficient mice, which were able to migrate to the parasite but were unable to kill the worms [24]. Although TLR4 and Gαi are linked in their activation and function [23,38], it can be concluded from the present study that Gαi2 protein is not required for TLR4-dependent neutrophil killing of the larvae. Neutrophils from TLR4-deficient mice cannot kill larvae [24], although they migrate to the site, whereas neutrophils from Gαi2-deficient mice can kill the larvae as efficiently as wild-type cells only if they are transported experimentally to the site of infection.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This is in contrast to neutrophils recovered from TLR4-deficient mice, which were able to migrate to the parasite but were unable to kill the worms [24]. Although TLR4 and Gαi are linked in their activation and function [23,38], it can be concluded from the present study that Gαi2 protein is not required for TLR4-dependent neutrophil killing of the larvae. Neutrophils from TLR4-deficient mice cannot kill larvae [24], although they migrate to the site, whereas neutrophils from Gαi2-deficient mice can kill the larvae as efficiently as wild-type cells only if they are transported experimentally to the site of infection.…”
Section: Discussioncontrasting
confidence: 51%
“…CXCR2 −/− mice have a defect in neutrophil recruitment and thus, a deficiency in the protective innate and adaptive immune response to larval S. stercoralis in mice [21]. Further study has shown that TLR4, which is linked to activation of Gαi-coupled signaling pathways [23], is required for activation of neutrophils [24]. Mice deficient in TLR4 fail to eliminate S. stercoralis infection, despite developing T and B cell immune responses and recruiting neutrophils to the parasite microenvironment [24].…”
Section: Introductionmentioning
confidence: 99%
“…Binding of TNF to the p55 TNFR leads to activation of a multiprotein signaling complex with release of silencer of death domains, recruitment of TNFR-associated death domain protein, and the adaptor proteins TNFR-associated factor 2 (TRAF2) and receptor-interacting protein, which ultimately activate MAPK and NF-B pathways involved in inflammation, proliferation, and apoptosis (53). Uncoupled receptor-dependent MAPK and NF-B signaling has been previously described for other TNFR superfamily members and TLR-4, either at the receptor level or through recruitment of other downstream components (54,55). Recent studies suggest that regulation of p55 TNFR and downstream components such as TRAF2 may also lead to divergent effects on MAPK and NF-B signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotrimeric guanine nucleotidebinding regulatory (Gi) proteins modulate LPS signaling pathways and downstream pro-inflammatory gene expression (4)(5)(6)(7). In addition to toll-like receptor (TLR) 4, LPS also binds to a cluster of receptors in lipid rafts, some of which are Gi protein coupled (8).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies demonstrated that LPS-induced inflammatory cytokines and chemokines were augmented in vitro and in vivo in Gi proteindeficient mice compared with WT mice, suggesting an anti-inflammatory role of Gi proteins (5,6). Gi protein-coupled ERK 1/2 signaling pathway mediates LPSinduced signaling (4). Activation of Gi protein with transforming growth factor-β (TGF-β) activates ERK 1/2, which can suppress NFκB and p38 signaling and consequently negatively regulate LPSinduced inflammatory responses (9,10).…”
Section: Introductionmentioning
confidence: 99%